Syntactic Interference of the Indonesian Language in Intermediate-Level German Composition - Rount Maulero; Hayatul Cholsy (Universitas Pendidikan Mandalika, 2026)
This study examines the phenomenon of syntactic interference arising from the structural differences between Indonesian (L1) and German (L2) in compositions written by B1-level students. The primary objective was to systematically identify, categorize, and analyze the specific forms of negative transfer. Utilizing the error analysis framework established by Corder and James, the data comprising 21 student compositions, were rigorously classified into systematic errors and incidental mistakes. The analysis revealed 15 distinct types of syntactic interference, predominantly involving critical German structures such as verb conjugation, word order (in both main and subordinate clauses), and the use of prepositions. The most frequently occurring form of negative transfer was observed in German verb conjugation errors. The overwhelming classification of observed instances as errors confirms a deep-seated negative transfer from the mother tongue to the target language system. These findings possess significant educational value, as they precisely map the areas where Indonesian speakers require the most targeted linguistic intervention. The results strongly recommend the integration of a contrastive learning approach and emphasize the urgent need for reinforcement activities that specifically build syntactic awareness in German instruction. This research serves as an evidence-based tool for practitioners, guiding the refinement of curriculum and pedagogical strategies to effectively minimize recurrent interference and enhance the precision of L2 acquisition at the intermediate level.